2012
DOI: 10.1186/1471-2091-13-15
|View full text |Cite
|
Sign up to set email alerts
|

The role of the C8 proton of ATP in the catalysis of shikimate kinase and adenylate kinase

Abstract: BackgroundIt has been demonstrated that the adenyl moiety of ATP plays a direct role in the regulation of ATP binding and/or phosphoryl transfer within a range of kinase and synthetase enzymes. The role of the C8-H of ATP in the binding and/or phosphoryl transfer on the enzyme activity of a number of kinase and synthetase enzymes has been elucidated. The intrinsic catalysis rate mediated by each kinase enzyme is complex, yielding apparent KM values ranging from less than 0.4 μM to more than 1 mM for ATP in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The specific activity of hAK1 and AKst in the direction of ATP synthesis (1 mM ADP as a substrate) was 87 ± 1 and 323 ± 4 U/mg of protein, respectively, whereas in the direction of ADP synthesis (AMP and ATP as substrates, 1 mM each) the activity was 463 ± 14 and 1100.6 ± 20 U/mg of protein, respectively. The specific activities of the recombinant enzymes were similar to that reported by other authors [ 43 , 57 , 58 , 59 ]. The CD spectrum and the calculated content of secondary structure showed that both recombinant AKs are predominately helical but with the significant content of β-sheet ( Figure S1B ).…”
Section: Resultssupporting
confidence: 88%
“…The specific activity of hAK1 and AKst in the direction of ATP synthesis (1 mM ADP as a substrate) was 87 ± 1 and 323 ± 4 U/mg of protein, respectively, whereas in the direction of ADP synthesis (AMP and ATP as substrates, 1 mM each) the activity was 463 ± 14 and 1100.6 ± 20 U/mg of protein, respectively. The specific activities of the recombinant enzymes were similar to that reported by other authors [ 43 , 57 , 58 , 59 ]. The CD spectrum and the calculated content of secondary structure showed that both recombinant AKs are predominately helical but with the significant content of β-sheet ( Figure S1B ).…”
Section: Resultssupporting
confidence: 88%
“…Additional functions include its role as a signalling molecule for posttranslational modification and catalytic functions within enzymes (Scheme ) 3. 5 From this large diversity of functions it becomes clear that describing ATP solely as energy currency in biochemistry is inadequate 6. ATP, therefore, is involved in many levels of biological function (Figure 1).…”
Section: Adenosine Triphosphate: More Than An Energy Currencymentioning
confidence: 99%
“…As described above, one important issue in applying cofactor‐dependent enzymes is cofactor regeneration. A range of efficient regeneration systems have been successfully developed for many organic enzyme cofactors, such as NAD(P)H 5. 31, 32 A key parameter for cofactor‐dependent enzymes within this context is the total turnover number (TTN), which indicates the moles of product formed per mole of cofactor during its entire life and represents a measure for catalytic efficacy.…”
Section: Atp Regenerationmentioning
confidence: 99%